Development of an Indian-adapted anti-inflammatory Mediterranean diet for coronary artery disease patients - Suparna Ghosh-Jerath; Archna Singh; Megha Suresh; Anudeep P P; Sherry Price; Sabiha Khan; Kamar Ali; Neha Bakshi; James R. Hebert; Ambuj Roy (BMC Nutrition)
Abstract Purpose Coronary artery disease (CAD) is a leading cause of death in India. Diet is an important modifiable risk factor associated with CAD. The Mediterranean Diet (MD), with its anti-inflammatory properties, is protective against CAD. Traditional Indian diets have several anti-inflammatory ingredients similar to MD. However, current Indian dietary analysis reveals high consumption of cereals with low legume, nut, fruit, and vegetable intake. In this study, we aimed to develop an anti-inflammatory Indian Adapted Mediterranean Diet (IAMD) using locally available anti-inflammatory ingredients. Methods We did a free listing of the foods that constitute a Mediterranean diet. Then, we matched Indian alternatives where specific Mediterranean foods could not be used due to non-availability or cultural acceptability. The Dietary Inflammatory Index (DII) scores were calculated for the developed menu to assess its anti-inflammatory potential. We also reviewed the diets of CAD patients and calculated the DII of their diets to understand their dietary intake and potential for replacing anti-inflammatory Indian food ingredients in their usual diets. Results The current DII of the diets consumed by CAD patients ranged from -1.8 to 3.8, with a median score of 1.1. After carefully compiling anti-inflammatory Indian food ingredients and incorporating them into routine diets, calorie- and nutrient-specific diet plans with a 7-day cyclic menu with North Indian recipes were developed, aligning with Mediterranean Diet principles. DII scores of the developed diet plans ranged from -7.8 to -8.4, with a median of -8.0, approaching the theoretical maximum anti-inflammatory score. Conclusions The IAMD developed with the lowest DII scores reported has the potential to be cardioprotective. However, this diet plan needs to be tested for acceptability and effectiveness in feasibility studies and clinical trials.